Symbolic Validation in Digital Football Transfer Communication on X: A Semantic Network Analysis of “Here We Go!” - Ardhi Fuady; Reza Safitri (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study examines the semantic structure of the phrase “Here We Go!” in football transfer communication on X using Semantic Network Analysis. Grounded in Communication Network Theory, the study explores how semantic relationships contribute to the construction of collective meaning and information credibility. Data were collected from 1,632 posts during the 2025 European summer transfer window and analyzed using NodeXL. The analysis included network metrics, degree centrality, word-pair analysis, and Clauset–Newman–Moore clustering. The findings indicate that the semantic network is dominated by concepts related to transfer confirmation, particularly deal, agreed, authorization, and sealed. Five thematic clusters were identified, representing transfer confirmation, contractual information, media dissemination, tactical aspects, and the core phrase itself. The results suggest that “Here We Go!” functions as a mechanism of symbolic validation through which audiences collectively recognize the credibility of football transfer information.